Simple Single-Pass Technique for Ultrathin Descemet Stripping Automated Endothelial Keratoplasty: A Pilot Study. Issue 10 (October 2017) - Dimitry, Maria E.S.; Lewis, Adam D.; Zacharaki, Fani; Chandran, Manju; Robson, Deana; Menon, Geeta; Poole, Thomas R. G.
Abstract : Purpose: To assess intraoperative and postoperative graft thickness (GT) after donor deturgescence for ultrathin Descemet stripping automated endothelial keratoplasty and to evaluate visual outcomes, endothelial cell density, and patient satisfaction at 1 year. Methods: Prospective interventional case series of patients with Fuchs endothelial dystrophy, Fuchs endothelial dystrophy and cataract, and pseudophakic bullous keratopathy (n = 12 grafts). The donor cornea was allowed to thin out by simple evaporation on an artificial anterior chamber, to the required precut thickness, before a single microkeratome pass. GT after microkeratome cut, at 1 week, 1, 3, 6, and 12, months was measured. Early Treatment Diabetic Retinopathy Study (ETDRS) best-corrected visual acuity, Pelli–Robson contrast sensitivity, endothelial cell density, and score on the visual function questionnaire (VFQ-25) were assessed. Results: Mean intraoperative postmicrokeratome cut GT was 78.9 ± 33.3 μm. Mean GT at 1 week, 1, 3, 6, and 12 months was 70.7, 70.9, 62.8, 66.5, and 58.9 μm, respectively. Mean initial donor corneal thickness was 647 ± 67 μm, and mean precut thickness was 526 ± 4.5 μm (mean thinning time: 17 min). Best-corrected visual acuity at 1 week, 1, 3, 6, and 12 months was 68.8, 76.9, 76.3, 76.9, and 78.6 letters with 9-letter gain at 12 months ( P = 0.02). Mean endothelial cell loss at 3, 6, and 12 months was 36.8% ± 6.75%, 37.2% ± 8%, and 37.9% ± 9.75% loss, respectively. At 1 year, 83.3% of patients achieved ≥20/40 (6/12) and 66.7% of patients achieved ≥20/32 (6/9.5). VFQ-25 testing showed an improvement in the visual function. Conclusions: This pilot study demonstrates a simple graft deturgescence technique that reproducibly creates ultrathin grafts without donor wastage.